Studies of the Specific Activity of Aerosolized Isoniazid against Tuberculosis in a Mouse Model - Sergey V. Valiulin; Andrey A. Onischuk; Anatoly M. Baklanov; Sergey N. Dubtsov; Galina G. Dultseva; Sergey V. An'kov; Tatiana G. Tolstikova; Sergey N. Belogorodtsev; Yakov Sh. Schwartz (MDPI AG, 2022)
The aerosol inhalation delivery of isoniazid in mice was investigated, and the specific activity of the aerosol form of isoniazid was studied with the mouse model of tuberculosis infection, the M. tuberculosis H37Rv strain. Aerosol delivery was performed using a laminar-flow horizontal nucleation chamber. The inhalation dose was measured in real-time mode using a diffusion aerosol spectrometer. The mean particle diameter was 0.6 ± 0.03 μm, and the inhalation dose was 5-9 mg/kg. Pharmacokinetic measurements were carried out in nose-only and whole-body chambers. Isoniazid concentration in blood serum and its mass in the lungs were measured as a function of time using high-performance liquid chromatography. Studies of the specific activity of aerosolized isoniazid reveal that treatment with the aerosol lead to the complete recovery of the experimental tuberculosis infection as early as after 28 days after the start of inhalation treatment, while in the animals from the group receiving isoniazid per-orally, sole revivable tuberculosis mycobacteria were detected. Histologic examinations show that only a few macrophagal (nonspecific) granulomas without mycobacteria were detected in the spleen after per-oral and aerosol treatment, the number of granulomas on the 28th day being three times smaller in the latter case. The results show that the developed technique of isoniazid aerosol inhalation may have clinical potential.